Monocyte Chemoattractant Protein-1 in Antineutrophil Cytoplasmic Autoantibody-Associated Vasculitis: Biomarker Potential and Association with Polymorphisms in the MCP-1 and the CC Chemokine Receptor-2 Gene - Nina Jönsson; Evelina Erlandsson; Lena Gunnarsson; Åsa Pettersson; Sophie Ohlsson (Hindawi Limited, 2018)
Antineutrophil cytoplasmic autoantibody- (ANCA-) associated vasculitis (AAV) are relapsing-remitting disorders with unpredictable prognosis. There is a need of biomarkers for distinguishing which patients will have a more severe outcome and also for predicting relapses in disease activity. This study confirms the previous results of urinary MCP-1 (uMCP-1) as a prognostic marker and explores its potential as a marker of disease activity. Method. 114 patients with AAV were followed regularly between 2002 and 2011 at Skåne University Hospital. Urine samples, blood samples, and clinical status were registered. The urine samples were analyzed in an in-house-developed ELISA. PCR-RLFP was used to analyze the MCP-1 and CCR2 genes. Results. Patients with severe prognosis had significantly higher levels of uMCP-1 compared to patients with nonsevere prognosis and healthy controls. Patients with renal damage had higher levels compared to patients who did not have renal damage. There was also a tendency of higher uMCP-1 levels in active disease as compared to remission. AA in the -2518 position in the MCP-1 gene was associated with a more severe outcome compared to the A/G or the G/G genotype. The A/A genotype were also associated with higher levels of uMCP-1. No significant associations were seen for the CCR2-V64I. Conclusion. This study confirmed the connection between high uMCP-1 levels and poor prognosis and also disease activity. It also suggests an association of the A/A genotype at position -2518 in the MCP-1 gene and poor prognosis in AAV. uMCP-1 is clearly a candidate biomarker of potential clinical value. The A/A genotype association needs further evaluation.